The Political Writings : "Political Regime" and "Summary of Plato's Laws" - Fārābī (Book collections on Project MUSE., 2001)
"Alfarabi was among the first to explore the tensions between the philosophy of classical Greece and that of Islam, as well as of religion generally. His writings, extraordinary in their breadth and deep learning, have had a profound impact on Islamic and Jewish philosophy. This volume presents four of Alfarabi's most important texts, making his political thought available to classicists, medievalists, and scholars of religion and Byzantine and Middle Eastern studies." "Butterworth situates each essay in its historical, literary, and philosophical context. His notes help the reader follow Alfarabi's text and identify persons, places, and events. English-Arabic and Arabic-English glossaries of terms further assist the reader."--Jacket